The risk of myocardial infarction, and social support among the population of 25-64 years in Russia/Siberia - V. V. Gafarov; E. A. Gromova; I. V. Gagulin; D. O. Panov; E. A. Krymov; R. R. Suleymanov; A. V. Gafarova (Российский кардиологический журнал)
Aim. To determine the impact of social support on the risk of myocardial infarction (MI) in an open population of 25-64 years in Russia/Siberia.Material and methods. As part of the III screening of the WHO MONICA-psychosocial program, a random representative sample of Novosibirsk population of both sexes aged 25-64 was examined (men: n=657, 44,3±0,4 years, response — 82,1%; women: n=689, 45,4±0,4 years, response — 72,5%). The screening survey program included: registration of socio-demographic data, definition of social support (ICC — indices of close contacts, SNI — social network index). The duration of the prospective observation of the participants was 16 years. First occurrences of MI were an endpoints of study.Results. We revealed that 62% of men and 56,8% of women had a low ICC (х2=22,603 df=2 P=0,0001). When distributed by age groups, the lowest ICC was observed in men in the 55-64 age group — 64,6% (х2=14,85 df=2 P=0,0001) and in 35-44 women — 60,6% (х2=3,917 df=2 P=0,141). Low SNI was among 43,5% of males and 33,9% of females (х2=21,546 df=2 P=0,0001). The lowest SNI among men was among the young age group of 25-34 years old — 50% (х2=15,894 df=3 P=0,001), for women — in the group of 35-44 years (39,4%) (х2=0,071 df=3 P=1). Over the 16-year observation period, Cox’s regression analysis showed an increase in the MI risk among persons with a low ICC index in men 5,2 (95% confidence interval (CI) 1,947-19,383; p<0,05) and women 4,9 times (95% CI 0,108-20,762; p<0,05). The risk of MI over a 16-year observation period in the single-factor Cox regression model was higher in individuals with a low SNI index, as among men OR=3,1 (95% CI 1,138-9,247; p<0,05) and among women, RR=2,9 (95% CI 1,040¬8,208; p<0,05). With the use of multivariate modeling, an increased risk of MI is found in people with low social support: among men with unfavorable family situation engaged in physical labor, and among women with a low level of education. Conclusion. Social support is a protective risk factor for MI in both men and women.